If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -52 = 4x + 32 Reorder the terms: -52 + -8x = 4x + 32 Reorder the terms: -52 + -8x = 32 + 4x Solving -52 + -8x = 32 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -52 + -8x + -4x = 32 + 4x + -4x Combine like terms: -8x + -4x = -12x -52 + -12x = 32 + 4x + -4x Combine like terms: 4x + -4x = 0 -52 + -12x = 32 + 0 -52 + -12x = 32 Add '52' to each side of the equation. -52 + 52 + -12x = 32 + 52 Combine like terms: -52 + 52 = 0 0 + -12x = 32 + 52 -12x = 32 + 52 Combine like terms: 32 + 52 = 84 -12x = 84 Divide each side by '-12'. x = -7 Simplifying x = -7
| -81+9x=88-4x | | 5=-50(2x-4)-2x | | 5x-63=117-4x | | -x-98=8x+37 | | -6-6x=16-5x | | 3*l= | | -47+2x=44-5x | | 75m-5-50m=1 | | 6(x+2)=5 | | -68+6x=75-5x | | 3(2x+1)-5=14-(x+14) | | -52-6x=3x+38 | | -2x-y=-1 | | -4(-1-2x)=35 | | -56+2x=22+8x | | 7x^2-x-12=0 | | -5x-4(-1-2x)=35 | | -2x-3+8x=-45 | | 32-34(65+56)=670 | | 99-4s-6s=-1 | | 32-6= | | -2x-12=6-3x | | 4nm+2sm-10n-5s=0 | | 4x^2-3x+17=0 | | 16r-8r=-1 | | -6x-68=103+3x | | 12x+3y=180 | | -5x-68=4x+40 | | 123x+56=6 | | -6x-69=35+2x | | 2+y=0 | | 9x-19=6x+47 |